A família Myrtaceae na Estação Ecológica do Panga, Uberlândia, Minas Gerais, Brasil (Lundiana: International Journal of Biodiversity, 2002)
A floristic survey of species of Myrtaceae was done in the Panga Ecological Station, located in the municipality of Uberlândia, state of Minas Gerais, Brazil, which comprises areas of different savanna (“cerrado”) physiognomies and forest formations. 36 species were found, distributed in nine genera: Eugenia with 12 species, Myrcia nine species, Psidium seven species, Campomanesia three species, and Calycorectes, Calyptranthes, Myrciaria, Myrcianthes and Plinia with one species each. For all taxa here treated we supply identifications keys, descriptions, distributions data and illustrations. Ecological observations show that the family is well represented in all vegetation formations except for wetlands.